(untitled) (Economics and region, 2025)
The article explores the institutional foundations of circular bioeconomy development, with a particular focus on the synergetic interplay between cluster policy and public–private partnership (PPP) mechanisms. The research emphasizes that the circular bioeconomy represents a multidimensional paradigm aimed at integrating sustainability principles into production and consumption models, while simultaneously strengthening innovation capacity and regional competitiveness. Special attention is given to the role of clusters as institutional mediators that connect small and medium-sized enterprises, research institutions, and public authorities, thereby facilitating knowledge transfer, coordination of value chains, and the development of innovative business models. The study synthesizes findings from recent international literature and policy documents of the European Union, highlighting that clusterization in Central and Eastern European countries has proven to be an effective tool for advancing regional entrepreneurial ecosystems and accelerating the transition to a circular bioeconomy. Furthermore, Northern European scholars underline the significance of “green development trajectories,” where clusters serve as mechanisms of institutional coordination in processes of ecological modernization. In this context, PPP arrangements are analyzed as powerful instruments for building circular infrastructure, mobilizing private investments, and ensuring efficiency in industrial waste management and bioresource utilization. In the Ukrainian case, the research outlines the potential of agricultural clusters to become drivers of post-war economic recovery and regional restructuring. It is argued that agro-bioeconomic clusters may serve as platforms for integrating local producers, scientific organizations, and municipal authorities into coherent regional ecosystems capable of enhancing resilience and ensuring sustainability. International reports and strategic foresight studies also point to the necessity of designing institutional roadmaps that combine cluster policy with PPP mechanisms to scale up the bioeconomy and integrate Ukraine more closely into the European circular economy framework. The findings provide both theoretical and practical contributions. From a theoretical perspective, the article expands the conceptual understanding of cluster policy as an institutional basis for fostering innovation-driven transitions in the bioeconomy. From a practical standpoint, the study offers applied recommendations for regional policymakers, local governments, and business stakeholders regarding the design of governance tools and partnership models that can accelerate the implementation of circular bioeconomy strategies. The results may be used for developing regional sustainable development strategies, formulating policy measures for industrial symbiosis, and elaborating roadmaps for circular transition in Ukraine and beyond.